Success Factors of Village-Owned Enterprises (Bumdes) in Indonesia - Safri; Jumanah; Tati; Lesmana, Bayu; Gunawan, Irfan; Sari, Ratna (Neo Journal of economy and social humanities, 2025)
This study discusses the factors that contribute to the success of Village-Owned Enterprises (BUMDes) as a strategic instrument in village economic development. The study begins with a general portrait of BUMDes in Indonesia that shows variations in performance and sustainability, followed by an explanation of the legal basis for the formation of BUMDes such as Law Number 6 of 2014 concerning Villages which emphasizes the importance of village economic independence. The urgency of establishing BUMDes lies in its ability to optimally manage local potential, increase village original income, and strengthen community participation in development. This study also highlights areas that have succeeded in developing BUMDes, such as in Central Java and Yogyakarta. which demonstrate good practices in village business governance and innovation. The key factors for the success of BUMDes include the availability of adequate capital and financial resources, human resource capacity and leadership quality, the suitability of business units with local village potential, active community participation and stakeholder support, and the implementation of governance and transparency. In addition, adaptive BUMDes management strategies, based on local potential, and upholding the principles of collaboration and professionalism are important aspects in ensuring business sustainability.